Ultraviolet disinfection of Schistosoma mansoni cercariae in water. - Lucinda Hazell (Public Library of Science (PLoS), 2021)
Background Schistosomiasis is a parasitic disease that is transmitted by skin contact with waterborne schistosome cercariae. Mass drug administration with praziquantel is an effective control method, but it cannot prevent reinfection if contact with cercariae infested water continues. Providing safe water for contact activities such as laundry and bathing can help to reduce transmission. In this study we examine the direct effect of UV light on Schistosoma mansoni cercariae using ultraviolet light-emitting diodes (UV LEDs) and a low-pressure (LP) mercury arc discharge lamp. Methodology S. mansoni cercariae were exposed to UV light at four peak wavelengths: 255 nm, 265 nm, 285 nm (UV LEDs), and 253.7 nm (LP lamp) using bench scale collimated beam apparatus. The UV fluence ranged from 0-300 mJ/cm2 at each wavelength. Cercariae were studied under a stereo-microscope at 0, 60, and 180 minutes post-exposure and the viability of cercariae was determined by assessing their motility and morphology. Conclusion Very high UV fluences were required to kill S. mansoni cercariae, when compared to most other waterborne pathogens. At 265 nm a fluence of 247 mJ/cm2 (95% confidence interval (CI): 234-261 mJ/cm2) was required to achieve a 1-log10 reduction at 0 minutes post-exposure. Cercariae were visibly damaged at lower fluences, and the log reduction increased with time post-exposure at all wavelengths. Fluences of 127 mJ/cm2 (95% CI: 111-146 mJ/cm2) and 99 mJ/cm2 (95% CI: 85-113 mJ/cm2) were required to achieve a 1-log10 reduction at 60 and 180 minutes post-exposure at 265 nm. At 0 minutes post-exposure 285 nm was slightly less effective, but there was no statistical difference between 265 nm and 285 nm after 60 minutes. The least effective wavelengths were 255 nm and 253.7 nm. Due to the high fluences required, UV disinfection is unlikely to be an energy- or cost-efficient water treatment method against schistosome cercariae when compared to other methods such as chlorination, unless it can be demonstrated that UV-damaged cercariae are non-infective using alternative assay methods or there are improvements in UV LED technology.